Pendidikan Kesehatan tentang Pemanfaatan Tanaman Herbal dalam Mengatasi Status Gizi pada Bayi dan Balita - Nurul Fatmawati; Yesvi Zulfiana; Irni Setyawati; Sri Handayani (Insan Kreasi Media, 2023)
Based on the weight for height index (WW/TB), the nutritional status of very thin toddlers is 3.5%, the nutritional status of underweight toddlers is 6.7%, and the nutritional status of obese toddlers is 8%. This service aims to provide health education about the benefits of herbal plants that pay attention to the nutritional status of babies and toddlers. This service method is participatory learning action, namely an approach to the learning process and interaction with the community or society. It is hoped that mothers can take advantage of these herbal plants because Moringa leaves, sweet potatoes and papaya contain many benefits, nutrients and vitamins that can improve the nutritional status of babies and toddlers. One of the benefits of papaya is that papaya can prevent digestive disorders in children's stomach organs which can affect their weight. The vitamin A content in Moringa leaf powder is 10 times higher than the vitamin A content in carrots and the vitamin C and iron content in sweet potatoes, making it beneficial for the growth and development of babies and toddlers. After implementing the PLA method service, the level of knowledge of mothers who had babies and toddlers with sufficient knowledge increased by 39% from 52% to 90.1%.